The Potential of Natural Source for The Development of Sport Tourism in Bone Bolango Regency - Rosbin Pakaya; Oktia Woro Kasmini Handayani; Soegiyanto KS; Sulaiman Sulaiman (International Conference on Science, Education, and Technology, 2023)
Taken place in Tomini Bay area, Bone Bolango has adequate tourism potential, including beaches, art, and cultural tourism through the quality of its attractions is very diverse and it is relatively unknown by outsiders. The natural attractions possessed include Olele Marine Park, Botutonuo Beach, Nani Wartabone Nature Reserve, Lombongo Waterfall, and the Botubarani Village Whale Shark Tourism. Furthermore, other unique features of Bone Bolango's natural tourism include: 1) being surrounded by mountains that are still very natural, 2) winding roads and also roads with steep inclines, 3) stretches of white sand, 4) clarity of the water, 5) presence of traders selling their goods, 6) information boards leading to the area, 7) safety information boards. The purpose of this study is to analyze the physical potential of Bone Bolango's natural resources, as well as its advantages and unique features. The research method used is descriptive qualitative with observation and interview techniques. The results show that Bone Bolango Regency has excellent natural physical potential, and the natural advantages of Bone Bolango Regency have the potential to be developed for sports tourism, and the unique natural attractions of Bone Bolango Regency include the Whale Shark Tourism as an attraction for sports tourism markets.